Ciril in Metod kot naslednika znamenitih dvojic v mitologiji, besedni umetnosti in zgodovini - Stanonik, Marija (Slavistična revija, 2018)
The Thessalonica brothers Cyril and Methodius are old saints, recognized by the Church. However, not one of the known texts from the Slovene territory comes close to the impressiveness of the saintly legend, let alone its criteria.
Keywords: Cyrillus; legende; Methodius; slovensko ljudsko slovstvo